2014
DOI: 10.1038/oncsis.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of enhancer of zeste homolog 2 (EZH2) activate tumor-suppressor microRNAs in human cancer cells

Abstract: Enhancer of zeste homolog 2 (EZH2) enhances tumorigenesis and is commonly overexpressed in several types of cancer. To investigate the anticancer effects of EZH2 inhibitors, microRNA (miRNA) expression profiles were examined in gastric and liver cancer cells treated with suberoylanilide hydroxamic acid (SAHA) and 3-deazaneplanocin A (DZNep). We confirmed that SAHA and DZNep suppressed EZH2 expression in AGS and HepG2 cells and inhibited their proliferation. The results of microarray analyses demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 46 publications
3
47
1
1
Order By: Relevance
“…Previous studies have showed that EZH2 was overexpressed in a variety of human cancers, which enhanced tumorigenesis through various signaling pathways [23]. In our study, downregulation of lncRNA-ANCR decreased the expression abundance of EZH2, suggesting that lncRNA-ANCR positively regulates the expression of EZH2.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have showed that EZH2 was overexpressed in a variety of human cancers, which enhanced tumorigenesis through various signaling pathways [23]. In our study, downregulation of lncRNA-ANCR decreased the expression abundance of EZH2, suggesting that lncRNA-ANCR positively regulates the expression of EZH2.…”
Section: Discussionsupporting
confidence: 64%
“…Because renal EMT and subsequent G 2 /M arrest are pivotal processes associated with overproduction of profibrotic cytokines and induction of renal fibrosis, EZH2 inhibitors would have therapeutic potential for treatment of renal fibrosis. Currently, several compounds for inhibition of EZH2 have been developed and are widely used in preclinical and in vitro studies to investigate the function of EZH2 in cancers and other diseases (60), and our data suggest a possible benefit from a clinical trial of treatment of renal fibrosis by EZH2 inhibition.…”
Section: Discussionmentioning
confidence: 73%
“…33 Currently, this compound is widely used in preclinical and in vitro studies to investigate the function of EZH2 in cancer and has been shown to effectively inhibit cell proliferation, reverse epithelial-to-mesenchymal transition, and prevent tumor progression. 34 However, it remains unclear whether targeting suppression of EZH2 can also interfere with renal interstitial fibroblast activation and renal fibrosis development. (A and E) Normally cultured NRK-49F cells were treated with 3-DZNeP (0-10 mM) for 36 hours.…”
mentioning
confidence: 99%